2015
DOI: 10.1093/ecco-jcc/jjv218
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Symptom Burden in Individuals with Inflammatory Bowel Disease

Abstract: Individuals with inflammatory bowel disease experience a considerable number of symptoms and are burdened by both physical and psychological symptoms, particularly during active disease. Healthcare professionals' focus of assessment needs to be broadened to encompass multiple symptoms. Greater attention needs to be given to fatigue and psychological symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
92
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 44 publications
4
92
1
1
Order By: Relevance
“…One single-center cross-sectional study showed that fatigue has an inverse relationship with clinical and endoscopic remission, and that deep remission has lower rates of fatigue complaints compared to clinical remission only [7]. In another cross-sectional study of 247 patients with IBD, lack of energy was the most burdensome symptom, more so than gastrointestinal complaints, such as diarrhea [8]. Fatigue occurs in patients with IBD of all ages and both sexes, although some studies suggest a greater burden in women [9].…”
Section: Introductionmentioning
confidence: 99%
“…One single-center cross-sectional study showed that fatigue has an inverse relationship with clinical and endoscopic remission, and that deep remission has lower rates of fatigue complaints compared to clinical remission only [7]. In another cross-sectional study of 247 patients with IBD, lack of energy was the most burdensome symptom, more so than gastrointestinal complaints, such as diarrhea [8]. Fatigue occurs in patients with IBD of all ages and both sexes, although some studies suggest a greater burden in women [9].…”
Section: Introductionmentioning
confidence: 99%
“…Common IBD symptoms may include diarrhea, abdominal pain, gastrointestinal bleeding, weight loss, and psychological distress. 1 3 CD and UC patients experience periods of remission and relapse, the latter generally triggered by environmental factors and characterized by intensification of symptoms. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis is a chronic, idiopathic, and diffuse inflammatory condition 1 with clinical symptoms including bloody diarrhea, bowel urgency, hematochezia, abdominal pain, and lack of energy. 2,3 Inflammatory bowel diseases (IBDs) such as ulcerative colitis are thought to result from overly aggressive T-cellmediated immune responses to commensal bacteria in the gut, resulting in injury to the digestive tract. 2,4 Various factors may interact to cause this inappropriate T-cell response, including genetic susceptibility of patients, the population of bacteria in the intestinal lumen, and environmental triggers such as the use of nonsteroidal, anti-inflammatory drugs.…”
mentioning
confidence: 99%